The influence of EDFA’s configurations on the behavioral trends of gain and noise figure - Sellami , Ali; Al-Khateeb, Khalid A. Saeed; Belloui, Bouzid (2006)
Various configurations have been conceived and tested for improvement of the gain and noise figures in Erbium doped fiber amplifiers (EDFA’s). Single pass (SP), double pass (DP), triple pass (TP) and quadruple pass (QP), are employed in the investigation. The highest gain and highest noise figure (NF) of 54dB and 7dB respectively are obtained at -50 dBm input power with 90 mW pump power using the QP configuration, while and the lowest gain of 23dB and lowest NF of 3dB are obtained at -50 dBm input power with 90 mW pump power for SP configuration.